Convalescent plasma therapy in patients with COVID‐19. Issue 4 (9th July 2020) - Yiğenoğlu, Tuğçe Nur; Hacıbekiroğlu, Tuba; Berber, İlhami; Dal, Mehmet Sinan; Baştürk, Abdülkadir; Namdaroğlu, Sinem; Korkmaz, Serdal; Ulas, Turgay; Dal, Tuba; Erkurt, Mehmet Ali; Turgut, Burhan; Altuntaş, Fevzi
Abstract: There are currently no licensed vaccines or therapeutics for COVID‐19. Anti‐SARS CoV‐2 antibody‐containing plasmas, obtained from the recovered individuals who had confirmed COVID‐19, have been started to be collected using apheresis devices and stored in blood banks in some countries in order to administer to the patients with COVID‐19 for reducing the need of intensive care and the mortality rates. Therefore, in this review, we aim to point out some important issues related to convalescent plasma (CP) and its use in COVID‐19. CP may be an adjunctive treatment option to the anti‐viral therapy. The protective effect of CP may continue for weeks and months. After the assessment of the donor, 200‐600 mL plasma can be collected with apheresis devices. The donation interval may vary between countries. Even though limited published studies are not prospective or randomized, until the development of vaccines or therapeutics, CP seems to be a safe and probably effective treatment for critically ill patients with COVID‐19. It could also be used for prophylactic purposes but the safety and effectiveness of this approach should be tested in randomized prospective clinical trials.